Optimization of Polyhydroxybutyrate Production by Bacillus safensis EBT1. Issue 8 (12th May 2016) - Madhumathi, Ramasamy; Muthukumar, Karuppan; Velan, Manickam
Abstract : The present study deals with the enhanced production of polyhydroxybutyrate (PHB) using a novel potent strain. On the basis of morphological, biochemical, and 16S rRNA analysis, the strain was identified as Bacillus safensis EBT1. The presence of PHB in the cells was identified and affirmed using fluorescent microscopy and Fourier transform infrared spectroscopy. The molecular weight of PHB was ascertained by gel permeation chromatography. Under optimized conditions, B. safensis EBT1 showed maximum PHB production and growth with glucose as the carbon source, yeast extract as the nitrogen source, and sugarcane bagasse as the substrate. The process parameters were optimized using central composite design: pH 7, 45 °C and 48 h incubation time. At these conditions, highest biomass concentration of 7.54 g/L and PHB production of 6.41 g/L were observed. Abstract : Polyhydroxybutyrate (PHB) is produced using a novel, potent strain Bacillus safensis EBT1, with sugarcane bagasse as substrate and glucose and yeast extract as carbon and nitrogen sources, respectively. Optimization using central composite design results in pH 7, 45°C and 48 h incubation time as the optimum conditions. Maximum biomass of 7.54 g/L and PHB production of 6.41 g/L is achieved.